Digital Transformation in Financial Management: Harnessing Technology for Business Success - Avira, Silvia; Rofi'ah; Setyaningsih, Endang; Utami, Suryandari Sedyo (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
Digital transformation in financial management has become the main focus for companies to achieve business success in the digital era. This research then aims to see the effect of digital transformation in financial management on efficiency, risk management, relations with external parties, and financial decision-making. The research method used in this research is qualitative research through library research. The data used in this study comes from the results of previous research and studies. The results of the study show that digital transformation in financial management brings significant benefits, such as increased operational efficiency through the automation of financial processes, real-time access to financial data for faster and more accurate decision-making, and improved relations with external parties through increased accessibility and the quality of financial services. However, challenges such as the security and privacy of financial data, cultural changes, and choosing the right technology solutions must also be addressed with care. To succeed in digital transformation in financial management, companies must adopt a strategic approach, mitigate risks, and engage stakeholders effectively.